2016
DOI: 10.1108/jap-09-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

Independent advocacy in adult support and protection work

Abstract: Structured abstractPurpose: This paper considers independent advocates' perspectives on their roles in Scottish Adult Support and Protection (ASP) work, and the facilitators and barriers impacting on these roles in practice.Design/methodology/approach: Semi-structured interviews were conducted with twenty managers and staff from six independent advocacy agencies operating across nine local authority areas.Findings : Participants described key roles in supporting individuals to understand their rights and to ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Whilst advocacy may be provided to a proportion of service users who attend case conference, our findings suggest it is not offered/suggested in a standardised way to everyone involved in ASP processes. These findings chime with those of Sherwood-Johnson (2016) and their investigation of independent advocacy which suggests that the low use of advocacy could be explained by the lack of knowledge of the services, and incorporating advocacy services within statutory frameworks could be considered to improve the use of advocacy services. Although the Act suggests that advocacy support is only required to be considered by the social worker, and offered where an individual has a diagnosed mental health condition, it is perhaps something which requires further consideration.…”
Section: Discussionsupporting
confidence: 55%
“…Whilst advocacy may be provided to a proportion of service users who attend case conference, our findings suggest it is not offered/suggested in a standardised way to everyone involved in ASP processes. These findings chime with those of Sherwood-Johnson (2016) and their investigation of independent advocacy which suggests that the low use of advocacy could be explained by the lack of knowledge of the services, and incorporating advocacy services within statutory frameworks could be considered to improve the use of advocacy services. Although the Act suggests that advocacy support is only required to be considered by the social worker, and offered where an individual has a diagnosed mental health condition, it is perhaps something which requires further consideration.…”
Section: Discussionsupporting
confidence: 55%
“…However, from the author’s experience of the embryonic stages of the ASP Act, it was not uncommon for the person to be absent from their APCCs. The UK studies both pre and post MSP indicate similar exclusionary practices (Fyson and Kitson, 2012; Jeary, 2004; Montgomery et al , 2017; Redley et al , 2015; Sherwood-Johnson, 2016). Certain groups including older people with dementia were found to be regularly excluded (Hopkinson et al , 2015; Wallcraft, 2012).…”
Section: Introductionmentioning
confidence: 90%
“…This paper uses the findings of MSP studies in England (Butler and Manthorpe, 2016; Cooper et al , 2018; Hopkinson et al , 2015) to highlight some of the issues identified within the case scenarios. Similarly, the discussion about the benefits of advocacy draws on research by Lonbay and Brandon (2017) and Sherwood-Johnson (2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations